Yield of next generation sequencing in diagnostic work up of suspicious biliary strictures - Tina L.N. Meijering; David Michaël de Jong; Swip Draijer; Marco Bruno; H. J. Dubbink; Jeroen de Jonge; Marie-Louise F. van Velthuysen; Lydi Van Driel (Endoscopy International Open)
Background This study addresses the need for improved diagnostic tools to identify malignancy in suspicious biliary strictures. Traditional cytological morphology is often indecisive, prompting the exploration of Next Generation Sequencing (NGS) for enhanced sensitivity. Our aim is to evaluate NGS's additional value in classifying biliary brushes and biopsies and its impact on Clinical Decision Making (CDM).